5(-9+x)=-25

Simple and best practice solution for 5(-9+x)=-25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-9+x)=-25 equation:


Simplifying
5(-9 + x) = -25
(-9 * 5 + x * 5) = -25
(-45 + 5x) = -25

Solving
-45 + 5x = -25

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '45' to each side of the equation.
-45 + 45 + 5x = -25 + 45

Combine like terms: -45 + 45 = 0
0 + 5x = -25 + 45
5x = -25 + 45

Combine like terms: -25 + 45 = 20
5x = 20

Divide each side by '5'.
x = 4

Simplifying
x = 4

See similar equations:

| 6(2+x)=72 | | -2x-30=28-4x | | (3)*(2x+9)=27 | | -8u-30=-6(u+7) | | -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x | | 3x-6(1+x)=-9x+9 | | 3b-50=4b-74 | | -124+12x=5x+86 | | 9x^2+4x+87=180 | | 6a+70=a | | 8x-151=49-2x | | 5x+3x-9=15 | | 3m^2-7m-40=0 | | -126+9x=39-2x | | -12-2x=-20 | | -93+4x=-6x+107 |

Equations solver categories